SENSE PROCESSES IN TOURISM BOOKLETS - Shanty Dwi Krishnaningsih (Elite : English and Literature Journal, 2020)
This research tries to analyze the processes of sensing found in tourism booklets. Since the research only focuses on the processes of sensing, it is focused on the verbs. The data are collected from two booklets from Latvia’s official tourism website. The method used is descriptive-qualitative. This analysis tries to answer three questions. They are the analyses of the sense processes, the types of sense processes, and the most and least sensing process verbs found from the analyses. From the analyses of the data, the emotive ‘like’ type verbs appear more than the other three sensing type verbs. The least finding is a desiderative verb, the verb wish.